2000
DOI: 10.1083/jcb.148.5.931
|View full text |Cite
|
Sign up to set email alerts
|

Pex19 Binds Multiple Peroxisomal Membrane Proteins, Is Predominantly Cytoplasmic, and Is Required for Peroxisome Membrane Synthesis

Abstract: Peroxisomes are components of virtually all eukaryotic cells. While much is known about peroxisomal matrix protein import, our understanding of how peroxisomal membrane proteins (PMPs) are targeted and inserted into the peroxisome membrane is extremely limited. Here, we show that PEX19 binds a broad spectrum of PMPs, displays saturable PMP binding, and interacts with regions of PMPs required for their targeting to peroxisomes. Furthermore, mislocalization of PEX19 to the nucleus leads to nuclear accumulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
320
5

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(353 citation statements)
references
References 54 publications
28
320
5
Order By: Relevance
“…Pex19p interacts with multiple PMPs (Gö tte et al, 1998;Sacksteder et al, 2000;Snyder et al, 2000;Fransen et al, 2001); however, precise Pex19p-binding sites have not yet been dissected and the physiological role of these interactions is under debate. We show here for the first time that Pex19p-binding sites represent short sequences that share a common motif and are integral parts of mPTSs and that these sites are required for the targeting of PMPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pex19p interacts with multiple PMPs (Gö tte et al, 1998;Sacksteder et al, 2000;Snyder et al, 2000;Fransen et al, 2001); however, precise Pex19p-binding sites have not yet been dissected and the physiological role of these interactions is under debate. We show here for the first time that Pex19p-binding sites represent short sequences that share a common motif and are integral parts of mPTSs and that these sites are required for the targeting of PMPs.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only three peroxins with a potential role in PMP targeting have been identified, namely Pex3p (Hettema et al, 2000;South et al, 2000), Pex16p in mammals (South and Gould, 1999;Honsho et al, 2002), and Pex19p (Gö tte et al, 1998;Matsuzono et al, 1999;Snyder et al, 1999;Soukupova et al, 1999). In cells lacking any of these proteins, PMPs are either degraded or mistargeted to other subcellular compartments such as mitochondria, the endoplasmic reticulum (ER) and membranes of unknown origin (Ghaedi et al, 2000;Hettema et al, 2000;Sacksteder et al, 2000).In accordance with a distinct pathway, PMPs use neither PTS1 nor PTS2. The targeting signals of PMPs (mPTS) that direct and insert PMPs into the peroxisomal membrane have been determined for a number of PMPs of several species.…”
mentioning
confidence: 99%
“…In pulse-chase experiments, newly synthesized PMP70, another ABC protein on peroxisomal membranes, has been shown to be targeted to peroxisomes directly from the cytosol in H4IIE cells, although most proteins, which enter the ER, do so cotranslationally and are never present in the cytosol fraction (Imanaka et al, 1996). It has been also suggested that Pex19p binds newly synthesized PMPs including PMP70 and ALDP, and facilitates their insertion into peroxisomes (Matsuzono et al, 1999;Sacksteder et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Pex19p has been suggested to act as a membrane protein receptor, recognizing peroxisomal membrane proteins (PMP) after their synthesis in the cytosol on polyribosomes and recruiting them to the peroxisomal membrane, most likely with the help of other proteins (Sacksteder et al, 2000). Pex19p has been shown to interact with the domains of PMPs that are required for targeting to the peroxisomal membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Pex19p has been shown to be primarily a cytosolic protein that can interact with a number of peroxisomal membrane proteins (Gö tte et al, 1998;Snyder et al, 1999aSnyder et al, , 1999bSnyder et al, , 2000Hettema et al, 2000;Sacksteder et al, 2000). Every ortholog of Pex19p contains a consensus sequence for the addition of a lipid farnesyl moiety at its extreme carboxy terminus (for a review of protein prenylation, see Omer and Gibbs, 1994), although the importance of this addition to the function of Pex19p is uncertain.…”
Section: Introductionmentioning
confidence: 99%